PENGARUH GAYA KEPEMIMPINAN DAN TRUST TERHADAP KINERJA KARYAWAN PADA KOPERASI KARYAWAN REDRYING (KAREB) KABUPATEN BOJONEGORO - jurnalmap map; Imam Mukri; Mei Indrawati; Hidayat ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This research is to analyze leadership style and trust both partially and simultaneously influence the performance of employees of the Employee Cooperative (Kareb) of Bojonegoro Regency. This type of research is explanatory research, namely research that explains the causal relationship between variables through hypothesis testing. While discussing using quantitative related numbers. The population in this study were all employees of the Redrying Bojonegoro (Kareb) Employee Cooperative in the Bojonegoro Regency DC unit which collected 31 people who also took research samples. The research sampling technique uses a sampling census taken from a DC unit because this unit is a problem with the commitment of its employees. The results of the study show simultaneously the leadership style variables and trust significantly influence employee performance. Partial leadership style and trust have a significant influence on the performance of employees of the Redrying Employee Cooperative (Kareb) in Bojonegoro Regency. Among leadership and trust styles that have greater significance for employee performance is trust. Keywords: leadership style, trust, employee performance